Perbedaan Konseling Gizi Menggunakan Media Booklet dan Leaflet terhadap Pengetahuan Pasien Diabetes Melitus Tipe 2 di Poli Gizi RSUD dr. H. Andi Abdurrahman Noor - Pratiwi, Nita; Abdurrachim, Rijanti; Pratiwi, Niken; Mahpolah, Mahpolah (HB PRESS, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disorder affecting 589 million people worldwide in 2024, including 11.3% in Indonesia. While nutrition counseling is a cornerstone of DM management, conventional media such as leaflets often fall short in improving dietary compliance. This study aims to analyze the comparative effectiveness of booklets versus leaflets in enhancing the knowledge of patients with Type 2 DM. This quasi-experimental study employed a nonequivalent control group pretest-posttest design at Nutrition Clinic of dr. H. Andi Abdurrahman Noor Regional General Hospital. The sample included 32 patients with T2DM. The variables assessed were nutrition counseling using leaflets and booklets, and patient knowledge. Data were analyzed using the Wilcoxon and Mann–Whitney tests. The results showed a significant difference in knowledge before and after nutrition counseling using both leaflet and booklet (p=0.000). There was a significant difference in the average knowledge score between the leaflet and booklet groups (p=0.006), with the leaflet group increasing by 5.81, whereas the booklet group increased by 7.06. In conclusion, booklets were more effective in improving knowledge. DM patients are encouraged to use the booklet to enhance their understanding of the DM diet and support healthier daily eating habits.